DEVELOPING AUTHORIAL VOICE: A LONGITUDINAL STUDY OF DIGITAL STORYTELLING'S IMPACT ON ADOLESCENT L2 WRITERS’ SYNTACTIC COMPLEXITY - Wang Jun; Michael Johnson; Dyah Retno Wulan (Yayasan Adra Karima Hubbi, 2025)
Digital transformation in language education has reshaped how adolescent second language (L2) learners engage with writing, particularly through multimodal pedagogies such as digital storytelling, which offer new spaces for expression and identity construction. This study aims to investigate the longitudinal impact of digital storytelling on the development of syntactic complexity and authorial voice among adolescent L2 writers. A longitudinal mixed-methods design was employed involving forty-eight secondary school learners over one academic semester. Data were collected through three phases of digital storytelling scripts, analyzed using corpus-based syntactic complexity indices, complemented by qualitative textual analysis and learner reflections. The results demonstrate significant and sustained growth in syntactic complexity, including increased clause embedding, sentence elaboration, and structural variation across time. Qualitative findings indicate that these syntactic developments were closely associated with stronger authorial voice, reflected in clearer narrative stance, evaluative language, and enhanced writer presence. The findings suggest that digital storytelling supports syntactic development as a meaning-driven and functional process rather than a purely formal outcome. The study concludes that sustained integration of digital storytelling in L2 writing instruction can effectively foster both linguistic sophistication and expressive agency among adolescent learners, highlighting the pedagogical value of longitudinal, narrative-based digital writing practices globally today.